Village Fund in the Light of New Regulations - Michał Wójcik (Prawo Budżetowe Państwa i Samorządu)
The article analyses legal conditionality particular form of participatory budgeting which is village fund. His five-year term of office gave rise to a positive evaluation of the project and to make specific legislative changes in this area. This was done in the new law of the village fund of 21 February 2014, which regulates the formation of the fund and reimbursement of expenses. This work research to both the old and the new provisions of the act and the exegesis of the regulations of the year.